The Lived Experience of Divorcing Evangelicals and How Integrated, Empathetic, and Restorative Practice Can Disclose God to Them - Robert Hornby (Religions)
Approximately seven in twenty marriages end in divorce in the UK, causing anxiety, depression, and a lasting impact on children. British evangelicals may fare better than average but are not immune from divorce. Despite a rich body of theological literature offering perspectives on divorce contributed by British evangelical scholars, there have been no related empirical studies to examine the lived experience of divorced evangelicals or the pastoral practitioners who support them. My study captures this missing empirical data, finding that evangelical divorce is a life-changing trauma that church practices sometimes compound. In contrast, those who reported integrated, empathetic, and restorative practices in their church or on the Restored Lives course say they were better able to cope, heal, and find hope. Irrespective of the pastoral environment, God was reported to act with compassion. The study employed mixed qualitative methods to capture the empirical data, which were analyzed and brought into dialog with relevant evangelical academic theology and documented practice. I concluded that in the context of complex connections and disconnections between the evangelical domains of theory and practice, integrated, empathetic, and restorative approaches toward the divorced are possible, effective, and disclose a God of grace.